2022
DOI: 10.1186/s12870-022-03725-3
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic responses under combined bacterial blight and drought stress in rice reveal potential genes to improve multi-stress tolerance

Abstract: Background The unprecedented drought and frequent occurrence of pathogen infection in rice is becoming more due to climate change. Simultaneous occurrence of stresses lead to more crop loss. To cope up multiple stresses, the durable resistant cultivars needs to be developed, by identifying relevant genes from combined biotic and abiotic stress exposed plants. Results We studied the effect of drought stress, bacterial leaf blight disease causing Xan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…The predicted off‐target DEK domain‐containing chromatin‐associated protein‐encoding transcripts were unaltered in all plants (Figure 6c). Expression of another off‐target gene, RPS12 , involved in the pathogen defence response (Pal et al., 2022), was not changed in dsRNA‐CPP6‐treated plants (Figure 6d). We anticipated that silencing of SDIR1 in rice through dsRNA should also provide resistance against BLB caused by Xoo.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…The predicted off‐target DEK domain‐containing chromatin‐associated protein‐encoding transcripts were unaltered in all plants (Figure 6c). Expression of another off‐target gene, RPS12 , involved in the pathogen defence response (Pal et al., 2022), was not changed in dsRNA‐CPP6‐treated plants (Figure 6d). We anticipated that silencing of SDIR1 in rice through dsRNA should also provide resistance against BLB caused by Xoo.…”
Section: Resultsmentioning
confidence: 90%
“…Plant‐pathogenic bacteria can destroy whole crops if not controlled, they secrete effectors to hijack plant mechanisms to cause virulence (Ramu, Oh, et al., 2021). Many negative regulators are upregulated during pathogen infections along with effector‐hijacked genes (Pal et al., 2022). Much evidence has been reported on possible target genes for virus, insect and fungal resistance (Rank & Koch, 2021); however, no study has reported targeting plant genes to improve bacterial disease resistance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, the stress magnitude, order and duration play crucial roles in determining the morpho-physiological outcomes of combinatorial stresses (Mittler, 2006a;Anwar et al, 2021a;Nadeem et al, 2022). Stress magnitude refers to the relative or absolute intensity of individual stressors, such as the absolute temperature during heat or cold stress (Praat et al, 2021;Zhu et al, 2022a), the soil water content during drought stress (Ma et al, 2014), light availability during submergence (Mohanty, 2003;Vashisht et al, 2011;Sasidharan et al, 2018), or the days post infection (dpi) during pathogenesis (Pal et al, 2022). Additionally, the number of co-existing stressors during a combinatorial stress scenario is also an important factor in determining the outcome for the plant.…”
Section: Concepts Of Stress Interactionsmentioning
confidence: 99%